A Deliberation upon the Realm of Imagination According to Certain Philosophers and Mystics - Nasrullah Shameli; Wahideh اaddشd (حکمت اسرا, 2012)
The faculty of representation and the realm of imaginative forms, act as an intermediary between the intellectual and physical world. In the history of the Islamic philosophy, from FÁrÁbī’s time to the present, the question of imagination has been a very important topic and has contributed to solving a great deal of problems, such as the problem of cognition, connection of contingent to the Eternal, and the Hereafter. Some experts have considered this as a distinguishing characteristic of Islamic philosophy. In this study, we are seeking to present briefly opinions of al-FÁrÁbī, Ibn SīnÁ, Suhrawardī, MullÁ ÑadrÁ and Ibn al-ÝArabī on the realm of imagination so that we could deal with their points of agreement and disagreement in this issue.